"It Wasn't Until I Took the Reins and Said…." Power and Advocacy in Canadian Women's Narratives of Polycystic Ovary Syndrome Diagnosis and Treatment*. Issue 1 (2nd January 2023) - Soucie, Kendall; Tapp, Kenzie; Kobrosli, Jasmine; Rakus, Marissa; Katzman, Rachel; Schramer, Kristin; Samardzic, Tanja; Citron, Noelle; Cao, Peiwen
Abstract: Gaps in health-care services for women with polycystic ovary syndrome (PCOS) are not isolated incidents. They are systemic and disadvantage women. In this study, we explored the juxtaposition of power and agency in diagnosis narratives collected from 72 Canadian women diagnosed with PCOS. Using Braun and Clarke's inductive codebook thematic analysis, three themes of power were constructed: physicians as gatekeepers, oppression as intersectional, and antagonistic provider communications, leading to emotional and cognitive impacts. Themes of agency centered on education, active resistance strategies, and collective action. Implications for these findings are discussed in relation to women's health equity.